Is an ethics of bodily inclusion emerging in the glamorous world of fashion models? - Ferreira, Vítor Sérgio (2020)
Recent structural changes in the fashion industry have produced transformations in the fOflns of embodiment socially valued by the modeling industry. These transformations seem to move in thc direction of the democratization of the models' appearancc canon, and towards the diversification of corporeality welcomed in the fashion market. Drawing from this perspective, the objective ofthis article is to comprehend sociologically the conditions, meanings and some ofthe effects ofthose changes in a way that can point to the emergence of a new ethics that values inclusive forms of embodiment inside the glamorous and highly selective world offashion models. The discussion will bc cmpirically based on a set of semi-directed intcrviews conducted with a set of professional fashion bookers, as well as focus groups done with young fashion models.